Clinical characteristics and outcomes in patients with traumatic brain injury in China: a prospective, multicentre, longitudinal, observational study. Issue 8 (August 2020) - Gao, Guoyi; Wu, Xiang; Feng, Junfeng; Hui, Jiyuan; Mao, Qing; Lecky, Fiona; Lingsma, Hester; Maas, Andrew I R; Jiang, Jiyao; ,
Summary: Background: Large-scale studies are required to better characterise traumatic brain injury (TBI) and to identify the most effective treatment approaches for TBI. However, evidence is scarce and mostly originates from high-income countries. We aimed to describe the existing care for patients with TBI and the outcomes in China. Methods: The Collaborative European NeuroTrauma Effectiveness Research in TBI (CENTER-TBI) China registry is a prospective, multicentre, longitudinal, observational study done in 56 neurosurgical centres across China. We collected data of patients who were admitted to hospital with a clinical diagnosis of TBI and an indication for CT. Patients who were discharged directly from the emergency room were excluded. The primary endpoint was survival on discharge. Prognostic analyses were applied to identify predictors of mortality. Variations in mortality were compared between centres and provinces within China. Mortality was compared with expected mortality, estimated using the CRASH basic model. This study was registered with ClinicalTrials.gov, NCT02210221 . Findings: From Dec 22, 2014, to Aug 1, 2017, 13 627 patients with TBI from 56 centres were enrolled in the registry. Data from 13 138 patients from 52 hospitals in 22 provinces of China were analysed. Most patients were male (9782 [74%]), with a median age of 48 years (IQR 33–61). The median Glasgow Coma Scale (GCS) score was 13 (IQR 9–15), and the leading cause of injury was road-traffic incident (6548 [50%]). Overall, 637 (5%) patients died, including 552 (20%) patients with severe TBI. Age, GCS score, injury severity score, pupillary light reflex, CT findings (compressed basal cistern and midline shift ≥5 mm), presence of hypoxia, systemic hypotension, altitude higher than >500 m, and GDP per capita were significantly associated with survival in all patients with TBI. Variation in mortality existed between centres and regions. The expected 14-day mortality was 1116 (13%), but 544 (7%) deaths within 14 days were observed (observed to expected ratio 0·49 [95% CI 0·45–0·53]). Interpretation: The results show differences in mortality between centres and regions across China, which indicates potential for identifying best practices through comparative effectiveness research. The risk factors identified in prognostic analyses might contribute to developing benchmarks for assessing quality of care. Funding: None.